Environmental Stress Tolerance and Antioxidant Response of Palisadaperforata (Rhodophyta) from a Tropical Reef1. Issue 3 (2nd April 2021) - Vasconcelos, Juliane B.; Vasconcelos, Edson R. T. P. P.; Urrea‐Victoria, Vanessa; Bezerra, Patricia S.; Cocentino, Adilma L. M.; Navarro, Daniela M. A. F.; Chow, Fungyi; Fujii, Mutue T.
Abstract : In this study, we analyzed the antioxidant activity and total phenolic content of the intertidal seaweed Palisada perforata collected from different reef microhabitats (sheltered site, tide pool, plateau, and exposed site) along the coast of Pernambuco (Brazil). Both parameters were compared with the same parameters of this species grown in the laboratory under two experiments simulating temperature, salinity, and desiccation conditions found in the reef. After both experiments (temperature x salinity and desiccation), the algal photosynthetic performance was measured through chlorophyll fluorescence parameters using a pulse–amplitude modulation fluorometer to test their stress response. Palisada perforata likely underwent stress by desiccation due to tidal fluctuations rather than to temperature or salinity changes. This conclusion agrees with our observations of the plateau site´s specimens, which were exposed to both air and UV radiation during low tides and exhibited higher antioxidant activity to avoid oxidative damage. However, despite the environmental stress, the antioxidant activity remained low, suggesting that photoinhibition is a crucial protection mechanism against oxidative damage.